2013
DOI: 10.1139/cjm-2012-0674
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic microbial diversity in coffee cherries ofCoffea arabicafrom southeastern Brazil

Abstract: The microbiota associated with coffee plants may play a critical role in the final expression of coffee quality. However, the microbial diversity in coffee cherries is still poorly characterized. Here, we investigated the endophytic diversity in cherries of Coffea arabica by using culture-independent approaches to identify the associated microbes, ultimately to better understand their ecology and potential role in determining coffee quality. Group-specific 16S rRNA and 26S rRNA genes polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 50 publications
2
25
1
6
Order By: Relevance
“…Next, the material w as immersed tw ice in distilled w ater and phosphate buffer (0.05 mmol·L -1 ), pH 7, immersed in 70% ethanol (v/v) for one minute, kept in a container filled w ith sodium hypochlorite (5%) + 0.05% (v/v) Tw een-80 for five minutes, and then immersed for 30 s in 70% ethanol (v/v) before being immersed again in sodium hypochlorite + Tw een-80 for 15 min (Miguel et al, , 2016Oliveira et al, 2013). This process w as repeated once.…”
Section: Surface Sterilization Of the Eucalyptus Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the material w as immersed tw ice in distilled w ater and phosphate buffer (0.05 mmol·L -1 ), pH 7, immersed in 70% ethanol (v/v) for one minute, kept in a container filled w ith sodium hypochlorite (5%) + 0.05% (v/v) Tw een-80 for five minutes, and then immersed for 30 s in 70% ethanol (v/v) before being immersed again in sodium hypochlorite + Tw een-80 for 15 min (Miguel et al, , 2016Oliveira et al, 2013). This process w as repeated once.…”
Section: Surface Sterilization Of the Eucalyptus Leavesmentioning
confidence: 99%
“…Microbial diversity can also be studied by analyzing the total DNA of the microbiota extracted directly from the plant for processing using electrophoretic techniques . Studies using these techniques have contributed to a better understanding of the microbial community structure and have led to new perspectives and advances in ecological studies (Hoshino and Matsumoto, 2007;Oliveira et al, 2013;Da Silva et al, 2014). Thus, the present study aimed at evaluating the composition and diversity of the endophytic fungal community in eucalyptus leaves at the onset of the rainy period and during the rainy and dry periods.…”
Section: Introductionmentioning
confidence: 99%
“…Archaea represent the so-called third domain of life, and have only recently been described as important component of the moderate environment and the human microbiome (Probst et al, 2013). A few very recent publications have mentioned internal plant tissue colonization by members of the Archaea (Ma et al, 2013; Oliveira et al, 2013), but their distribution, significance, function, and activity remains unclear. In addition, the endophytic microbiota of trees has undergone less investigation and nothing is known about the associated microorganisms within olive trees.…”
Section: Introductionmentioning
confidence: 99%
“…These results extend current thinking, that multiple organisms within multiple taxonomic domains may be involved in the onset of disease or disease suppression in plants (Coats and Rumpho 2014). Most studies on microbial endophyte communities and dieback investigate one specific microbial taxon, typically fungi (Wilson and Pitkethley 1992;Diplock et al 2006;Kowalski and Holdenrieder 2009;Haque et al 2012;Ismail et al 2012;Sacdalan et al 2012), although there are exceptions (Mendes et al 2011;Knief et al 2012;Ma et al 2013;Oliveira et al 2013;Ruppel et al 2013). Our study found a very diverse microbial community (as assessed using OTUs) whose structure differed with plant health status.…”
Section: Discussionmentioning
confidence: 56%